Bir Yönetişim Hedefi Olarak Değer Optimizasyonu: Kalkınma Ajansları Üzerinden Bir Analiz. - EFE, Ahmet (Afyon Kocatepe University Journal of Social Sciences / Afyon Kocatepe Üniversitesi Sosyal Bilimler Dergisi, 2018)
Value creation, adding value and organizational value concepts are being related with corporate mission and vision as basic principles at the literature. However, there is no a specific framework or standard on how to create adding value at corporate level. Furthermore, rather than how to create adding value to organization, in fact the value optimization is concerned on how to optimize attainable and sustainable corporate value in accordance with risks and resources that need to be optimized. COBIT-5, proposes process model for value optimization which needs to be tailored according to organizational goals stemming from stakeholder needs. Because of the necessity of extensive digital conversion, e-government applications are constantly increasing, so the governance of IT systems and the co-operation of business processes have become a necessity in terms of value production. In this study, with a solution finding approach, our research problem defined for regional development agencies (KA) as inability to optimize value for regional governance and local development. It is argued that 5 out of 43 problems of KA defined in 2014 by State Auditing Board (DDK), that are somehow related with value optimization processes could be conceptually modelled for KA with a process model subdivided as assessment, direction and monitoring.